Synthesis and Characterization of Magnetic Nanoparticles as Contrast Agents for Tumor Imaging - Kiat, Ton; Lek, Siri; Thai, Aom; Muntasir, Muntasir (Journal of Biomedical and Techno Nanomaterials, 2024)
Magnetic nanoparticles (MNPs) have emerged as promising materials for biomedical applications, particularly as contrast agents in tumor imaging. Early and accurate tumor detection is critical for improving treatment outcomes, yet current imaging techniques often lack sensitivity and specificity. This study aimed to synthesize and characterize magnetic nanoparticles for their potential as contrast agents in tumor imaging. The nanoparticles were synthesized using a co-precipitation method, followed by surface modification with organic compounds to enhance stability and targeting specificity. Characterization included transmission electron microscopy (TEM), X-ray diffraction (XRD), vibrating sample magnetometer (VSM), and dynamic light scattering (DLS). Cytotoxicity and targeting efficiency were evaluated in vitro using cultured human tumor cells. The results demonstrated that the synthesized nanoparticles had an average size of 25 ± 5 nm, superparamagnetic properties with a saturation magnetization of 55 emu/g, and high colloidal stability due to surface modifications. Fluorescence imaging revealed significant accumulation of the nanoparticles in tumor cells, while cytotoxicity tests showed cell viability above 85% at concentrations up to 100 ?g/mL. These findings indicate the nanoparticles are safe and effective for tumor imaging. This study highlights the importance of integrating synthesis, characterization, and biological evaluation to optimize nanoparticle design for biomedical applications. While the results are promising, further in vivo studies are needed to evaluate nanoparticle distribution, accumulation, and clearance in complex biological systems. The findings provide a foundation for future research and development of advanced contrast agents for tumor imaging